APPLICATION OF CONTEXTUAL TEACHING AND LEARNING MODEL (CTL) TO IMPROVE READING UNDERSTANDING ABILITY - Suwardini, Tri Diani; Sulastri, Lilis; Altaftazani, Deden Herdiana (IKIP Siliwangi, 2018)
Reading is a very important language skill. Because by reading someone can increase knowledge. But in its implementation in school there are still many obstacles. Based on the results of research that students' reading ability in schools is still relatively low. Another problem in reading learning, which needs to be thought by all parties is the problem of competence and creativity of the teacher in compiling reading learning materials. Because the development of learning materials is very important in motivating student learning. Teachers must be able to compile learning materials that are appropriate to the conditions of the student's own environment. Contextual learning materials will motivate students in learning. The main problem in this study was